A Review of The Literature on An Examination of The Effects of Cyber Security in Improved Public Sector Institution Performance in Jordan - Saleem Alrkeebat, Alanoud Amer (International Journal of Scientific Research and Management (IJSRM), 2024)
Gaining a clearer knowledge of the present level of cyber security adoption by public sector institutions—particularly in Jordan—was one of the study’s intended results. In order to improve the effectiveness of these institutions, the research reviewed various literature review on the current state of cyber security adoption. It also identified the obstacles that these institutions faced in embracing and executing these technologies, as well as the tactics that were required to improve cyber security applications. The assessment also highlighted cyber security initiatives that can boost operational effectiveness, enhance service delivery, and give the populace of the nation access to a safer digital environment. Therefore, by highlighting the difficulties and obstacles these organizations encounter, the research may contribute to the formulation of policy and decision-making frameworks that will direct future expenditures on cyber security and associated technology. Additionally, the results of this study may help improve cyber security protocols and implement them in Jordan’s public sector organizations. This might thus result in better service delivery, more operational efficiency, and a safer online environment for the people of the nation. The study may also contribute to policy and decision-making processes by highlighting the obstacles and difficulties these organizations confront, which might direct subsequent investments within cyber security innovations and technology.